Magnetic Phase Transition in Spark-Produced Ternary LaFeSi Nanoalloys - Feng, Jicheng (ACS Appl Mater Interfaces, 2018)
[Image: see text] Using the magnetocaloric effect in nanoparticles holds great potential for efficient refrigeration and energy conversion. The most promising candidate materials for tailoring the Curie temperature to room temperature are rare-earth-based magnetic nanoalloys. However, only few high-nuclearity lanthanide/transition-metal nanoalloys have been produced so far. Here we report, for the first time, the observation of magnetic response in spark-produced LaFeSi nanoalloys. The results suggest that these nanoalloys can be used to exploit the magnetocaloric effect near room temperature; such a finding can lead to the creation of unique multicomponent materials for energy conversion, thus helping toward the realization of a sustainable energy economy.